Automatic Slides Generation for Scholarly Papers: A Fine-Grained Dataset and Baselines (Student Abstract) - Xu, Sheng; Wan, Xiaojun (Proceedings of the AAAI Conference on Artificial Intelligence, 2022)
Slides are broadly used to present the research works and there are several studies on the problem of automatic slides generation. However, the lack of dataset hinders further research. In this paper, we construct a benchmark dataset for the problem of slides generation from scholarly papers. The dataset is fine-grained and consists of aligned pairs of single slide and specific region of a paper. Then we deploy several baseline models and conduct preliminary experiments. The results show that this task is challenging and awaits more exploration. The dataset and code will be released.